2019
DOI: 10.1038/s41746-019-0192-z
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning can accurately predict pre-admission baseline hemoglobin and creatinine in intensive care patients

Abstract: Patients admitted to the intensive care unit frequently have anemia and impaired renal function, but often lack historical blood results to contextualize the acuteness of these findings. Using data available within two hours of ICU admission, we developed machine learning models that accurately (AUC 0.86–0.89) classify an individual patient’s baseline hemoglobin and creatinine levels. Compared to assuming the baseline to be the same as the admission lab value, machine learning performed significantly better at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…As the largest publicly available EHR ICU dataset, MIMIC has received intense interest from the AI/ ML community as a common ground for developing and validating new methods. For example, in terms of ICU sepsis treatment, MIMIC has been used in various AI/ML approaches ranging from gradient-boosting to reinforcement and deep learning (Komorowski et al, 2018;Dauvin et al, 2019;Kaji et al, 2019;Hou et al, 2020). Several projects have focused on predicting ICU mortality, producing results that include a decision support tool for determining optimal patient ICU discharge times to improve patient outcomes (McWilliams et al, 2019).…”
Section: Mimic Facilitates Ai/ml Research With Rwdmentioning
confidence: 99%
“…As the largest publicly available EHR ICU dataset, MIMIC has received intense interest from the AI/ ML community as a common ground for developing and validating new methods. For example, in terms of ICU sepsis treatment, MIMIC has been used in various AI/ML approaches ranging from gradient-boosting to reinforcement and deep learning (Komorowski et al, 2018;Dauvin et al, 2019;Kaji et al, 2019;Hou et al, 2020). Several projects have focused on predicting ICU mortality, producing results that include a decision support tool for determining optimal patient ICU discharge times to improve patient outcomes (McWilliams et al, 2019).…”
Section: Mimic Facilitates Ai/ml Research With Rwdmentioning
confidence: 99%
“…ML has successfully been applied to the intensive care unit (ICU) setting, to accurately predict preadmission hemoglobin and creatinine in patients. 54 The model uses clinical data commonly available within the first few hours of ICU stay, with predictions averaging within 0.3 to 0.4 mg/dL of actual creatinine values. 54 Having accurate predictions of a patient's baseline creatinine would be indispensable to guide the modality as well as the intensity of treatment.…”
Section: Future Directions and Conclusionmentioning
confidence: 99%
“…Recent advances in Artificial Intelligence have shown that deep learning applied to medical images can identify phenotypes beyond what is currently possible by observation from human clinicians alone [8] , [9] , [10] , [11] . Such discoveries have spanned across a variety of imaging modalities in many medical specialties and have uncovered imaging correlates for a wide range of disease states, molecular signatures, and physiologic conditions [12] , [13] , [14] , [15] .…”
Section: Introductionmentioning
confidence: 99%